The effect of rocker ratio and connecting rod length on the performance of a crank-rocker mechanism with an extended rocker input link - Mohammed, S.E. (Asian Research Publishing Network, 2016)
The effect of the rocker ratio, and the distance between the crank and rocker extreme positions, of a general four-bar mechanism with an extended rocker arm length are analyzed. The crankshaft rotation was set at a constant rate of 2000rev/min, and all mechanisms had the same strokes. A constant input force of 100N was applied at the rocker tips of all the mechanisms having a unit ratio of 1. A computer program using MATLAB code was developed for the kinematic and dynamic analysis of the crank-rocker mechanism to solve the governing equations. The results obtained from aforementioned analysis were plotted, compared and verified with the results obtained from ADAMS Software. It is concluded that the variation of rocker ratio did not have any effect on the rocker angular acceleration and torque output. However, a shorter distance, i.e. shorter connecting rod, is better than a longer connecting rod in terms of the peak values of angular acceleration and torque output. The results of the analytical solution were in good agreement with those obtained from ADAMS within 2 error. The findings are very significant for the improved design of the mechanism in term of power and packaging advantages. Â© 2006-2016 Asian Research Publishing Network (ARPN).